Reduced cerebrospinal fluid concentration of interleukin-12/23 subunit p40 in patients with cognitive impairment - Johansson, Per; Almqvist, Erik G.; Wallin, Anders; Johansson, Jan-Ove; Andreasson, Ulf; Blennow, Kaj; Zetterberg, Henrik; Svensson, Johan (PloS one, 2017)
The role of inflammation in Alzheimer's disease (AD) and other cognitive disorders is unclear. In a well-defined mono-center population, we measured cytokines and chemokines in paired serum and cerebrospinal fluid (CSF) samples. Consecutive patients with AD (n = 30), stable mild cognitive impairment (SMCI, n = 11), other dementias (n = 11), and healthy controls (n = 18) were included. None of the subjects was treated with glucocorticoids, cholinesterase inhibitors, or non-steroidal anti-inflammatory drugs. Serum and CSF concentrations of interleukin-6 (IL-6), IL-8, IL-12/23 p40, IL-15, IL-16, vascular endothelial growth factor-A (VEGF-A), and three chemokines were measured using a multiplex panel. After correction for multiple comparisons, only CSF IL-12/23 p40 concentration differed significantly between the total patient group (n = 52) and controls (n = 18; p = 0.002). Further analyses showed that CSF IL-12/23 p40 concentration was decreased in all patient subgroups (AD, other dementias, and SMCI) compared to healthy controls (p < 0.01, p < 0.05, and p < 0.05, respectively). In the total study population (n = 70), CSF IL-12/23 p40 concentrations correlated positively with CSF concentrations of β-amyloid1-42 (Aβ1-42) and phosphorylated tau protein (P-tau) whereas in AD patients (n = 30), CSF IL-12/23 p40 only correlated positively with CSF P-Tau (r = 0.46, p = 0.01). Most cytokines and chemokines were similar in patients and controls, but CSF IL-12/23 subunit p40 concentration was decreased in patients with cognitive impairment, and correlated with markers of AD disease status. Further studies are needed to evaluate the role of CSF IL-12/23 p40 in other dementias and SMCI.